PENGARUH BUDAYA ORGANISASI TERHADAP KUALITAS PELAYANAN PUBLIK (STUDI KASUS PADA KANTOR UNIT PELAYANAN TERPADU (UPT) SAMSAT MEDAN SELATAN) - Lubis, Khairunnisah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2022)
A state agency that has a good work culture can be seen and observed by the people who receive public services. This can also be seen at the South Medan Samsat Integrated Service Unit (UPT) Office. UPT Samsat South Medan is a representative of a Government Institution which is engaged in providing services to the public, namely in the form of motor vehicle ownership management services to the public. The public's views on the quality of service at the South Medan SAMSAT UPT Office vary, but in general the quality of the service provided is quite satisfactory to the public.